Version Locking Mechanism in Database (International Journal of Innovative Research in Computer Science & Technology, 2020)
The distributed database provides a resource  sharing environment, where multiple transactions at different  sites coexist in order to access the resources. In this paper we  investigate multi version locking protocol in distributed  environment. Multi-version database has the potential to  significantly increase the amount of concurrency in  transaction processing as they can avoid read-write conflict by completing the read requests with older versions of data  while the write operation is in progress. These algorithms are  particularly effective for long queries, which otherwise  cannot finish due to the high probability of conflict with  other transactions. We have given an improvement on the  algorithm proposed by Jie shao. We have not imposed any  restriction on the involvement of all the existing sites to  obtain a global version which thereby reduces the burden on  each individual site. Our scheme involves the collection of  local transaction identifier only from the participating site  whether it can be one or many. We have proposed our new  algorithm to obtain a correct version for a particular data  item during read and write operation.
Keywords: Local transaction identifier; Global consistent snapshot version; Serializability